THEMATIC PROGRESSION ANALYSIS ON STUDENTS’ ANALYTICAL EXPOSITION TEXTS - Asep Saepuloh (Bajang Institute, 2023)
This study aims to investigate how university students organize their ideas in Exposition texts, particularly Analytical Exposition texts, and to what extent their Analytical Exposition texts are consistent with argumentative language features in terms of Thematic Progression, based on the framework of Systemic Functional Linguistics. The data were taken from nine Analytical Exposition texts of university students at low, moderate, and high levels of achievement. The result shows that the students organize their ideas in three ways of Thematic Progression namely Constant Theme Theme Progression (CTP) or Re-iteration pattern, Simple Linear Theme Progression (SLP) or Zig-Zag pattern, and Derived Theme Progression (DTP) or Multiple Theme pattern. In terms of Thematic Progression consistency, some texts from middle and high achievers are consistent with the argumentative language features, since they employed SLP than CTP and DTP. However, some students still need more guidance to improve the quality of their writings